Determinants of Customer Trust in Universities: A Study of Private Universities in Banten, Indonesia - Alfatiyah, Rini; Limakrisna, Nandan; Muharam, Hari (International Journal of Management and Digital Business, 2023)
This study aims to determine and analyze the impact of Brand Image, service quality, and Customer Relationship Management on customer trust in private universities in Banten. The type of research used is descriptive survey research and explanatory research with verification methods. The study population was students from five universities in Banten, with the most significant number of students in South Tangerang; in this study, the sample size is determined in the form of statistical tests that will be used as a model of structural Equation Modeling (SEM), while the determination of the minimum number of samples in this study is to use the Slovin formula according to Sevilla, 1998—a selection of 354 respondents. Questionnaires collected data. The Data were analyzed by structural equation modeling (SEM) and its tools using Lisrel 8.80. The results revealed that brand image has a positive and significant effect on customer trust, Service Quality has a positive and significant impact on customer trust, and Customer Relationship Management has a positive and significant effect on customer trust.